A new model for the spread of the first farmers in Europe - Pinhasi, Ron (Documenta Praehistorica, 2003)
The appearance and dispersion of the first farmers in Europe has been the subject of heated debate among anthropologists, archaeologists, and linguists for over a century. There is no consensus regarding two main aspects: (1) the extent to which the transition to farming was an indigenous process, and (2) the historical pattern in terms of the timing and tempo of the dispersion events. Morphological variability and affinities are assessed among Mesolithic and Early Neolithic populations of the Near East, Anatolia and Europe. Statistical results reveal regional and temporal differences in the dispersion process among these populations. Based on these results, a new model is presented for the spread of farming in Europe.
Keywords: archaeology; arheologija; mezolitik; neolitik; Europe; Evropa; Levant; Anatolija; kraniometrična analiza; biološke distance; morfološka variabilnost